OFFENCES AGAINST SECURITY ACTIVITIES: ANALYSIS OF OBJECTIVE ELEMENTS OF CRIMINAL OFFENCES AND SIGNS OF CORPUS DELICTI THAT CHARACTERISE THEM (Bulletin of criminological association of Ukraine, 2023)
The scientific publication is devoted to the analysis of objective elements of the main (basic) criminal offences against security activities (Articles 197, 342, 343, 345, 347, 348, 367, 380, 381, 387, 396 of the Criminal Code of Ukraine) and the signs of corpus delicti which characterise them, taking into account the provisions of the current criminal legislation of Ukraine, as well as the existing doctrinal positions on this issue. It is noted that a systematic analysis of the objective elements of the main (basic) criminal offences against security activities (Articles 197, 342, 343, 345, 347, 348, 367, 380, 381, 387, 396 of the Criminal Code of Ukraine) as phenomena of real reality and the signs of corpus delicti which characterize them allows to identify the specifics of generic, specific and direct objects of corpus delicti of these criminal offences. For example, the specificity of the generic object of these criminal offences is that such a generic object is the sphere of security activities, within which the procedure for performing duties to protect property or life of citizens ensures the right to property, authority of public authorities, law enforcement agencies and associations of citizens, normal official activities in certain legal entities of public or private law, as well as the safety of life or property of persons during pre-trial investigation or administration of justice.The author proves that a specific feature of certain types of these criminal offences is their multi-objective nature. This cannot but affect the qualification, since depending on which direct objects contained in some of these criminal offences are encroached upon by a person, the assessment of the act may be carried out both by a set of criminal offences and by any single such criminal offence. In this regard, the analysis of corpus delicti that characterize the objects of some of these criminal offences is of great importance in law enforcement.
Keywords: security activities; criminal offences; object; objective side; corpus delicti of a criminal offence; socially dangerous consequences; grave consequences; safety of persons taken under protection